Pengaruh Penambahan Azolla Microphylla Pada Pakan Basal Berbentuk Pelet Terhadap Karakteristik Karkas Entok (Cairina Moshata) - Rohmah, Anisa Aulia; Djunaidi, Irfan H; Tistiana, Heli (Jurnal Teknologi Hasil Peternakan, 2024)
The large number of water fern that are still not utilized can be used as animal feed, especially muscovy ducks because they have a fairly high protein content. This research aimed to evaluate the effect of adding water fern (Azolla microphylla) to basal feed in the form of pellets on the characteristics of duck carcasses (Cairina moshata). The material used was 60 day old duck (DOD) males and females (unsex). The method in this study was an in vivo experiment using a completely randomized design (CRD) with 3 treatments and 5 replicates. The treatment consisted of giving basal feed in the form of pellets and Azolla as much as 0% (P0), 5% (P1), and 10% (P2). Variables measured in this study included live weight, carcass weight, % carcass, % breast, % thigh, % back, and % wing. The data obtained were then analyzed using Analysis of Variance (ANOVA) and continued with the smallest real difference (BNT). The results showed that the treatment had no significant effect (P>0.05) on % carcass, % breast, % thigh, % back, and % wings but had a very significant effect (P<0.01) on live weight and carcass weight. The addition of Azolla microphylla to the basal feed in the form of pellets to the carcass characteristics of muscovy duck (Cairina moshata) up to a level of 10% can increase live weight and carcass weight.